Can multicultural human resources management problems be solved by an organisational culture? - Karjalainen, Helena (Management international / Gestiòn Internacional / International Management)

(untitled) (HEC Montréal et Université Paris Dauphine, 2010)
During recent decades, globalisation has affected and changed functions of enterprises, firms must adapt their strategies to global business and to international human resources management. A new challenge seems to be imposed to international managers and to international HRM: how to create cooperation between employees representing different cultural backgrounds and how to find a common identity in multicultural teams? Our article, based on a case study, inter-site cases, examines five different multicultural work groups. Results reveal how cooperation can be created and managed with the HRM practices and tools: recruitment, intercultural management, mediation and organisational culture.